EFEK INSENTIF PERPAJAKAN BERDASARKAN DASAR PENGENAAN PAJAK DAN TARIF PAJAK TERHADAP EKONOMI SECARA MAKRO : STUDI KASUS INDONESIA - Mohammad, Ryan; Helmi Zus Rizal; Gede Satria Pujanggo, PG (Scientax, 2021)
Due to National Economy Recovery program, the Indonesian Government had conducted severalTax Incentive Policies to escalate economic growth faster. However, we have not found any studyto measure the policies' effect on macroeconomic indicators. In this paper, we attempt to find theimpact of Tax Incentive Policies that had been implemented for the end of the year of 2018. Ourpurpose is solely to find general understanding and knowledge about Tax Incentive Policies' effecton Macroeconomy. Based on the examination test using The Impulse Response Function method,we discovered that Tax Incentive Policies positively impact Investment, gross domestic product, and unemployment.Specifically, Tax Incentive Policies based on Tax Rates have a better positive impact than TaxIncentive Policies based on Tax Base. However, those impact only relatively sustains in a short period.